The Effect of DevOps Implementation on Teamwork Quality in Software Development - Ady Hermawan; Lindung Parningotan Manik (Journal of Information Systems Engineering and Business Intelligence, 2021)
Background: The Agile method, which is claimed to reduce time needed for software development cycle has been widely used. It addresses communication gaps between customers and developers. Today, the DevOps has been extended as part of the Agile process to address communication gaps between developer’s team members. Despite the rising popularity, the effect of DevOps implementation on the teamwork quality in software development is still unknown.Objective: The objective of this research is to conduct a study on the impact of DevOps on teamwork quality. Two software houses, PT X and PT Y, are chosen as the case studies.Methods: This research uses quantitative methods to analyse research data using simple linear regression. The questionnaire technique is used to retrieve respondent data using 62 questions, consisting of 20 DevOps questions from 4 indicators and 42 teamwork quality questions from 6 indicators.Results: The results from various quality tests indicate that all instruments are valid and reliable while hypothesis tests showed that the DevOps implementation variable has an influence on the teamwork quality variable by 75.6%.Conclusion: It can be concluded that the implementation of the DevOps in software development has a positive correlation with the teamwork quality.